MEDIA ETHICS IN WARTIME: THE CODE FOR THE COVERAGE OF THE COLOMBIAN ARMED CONFLICT - Serrano, Yeny (Ciudad Paz-ando, 2014)
By analysing the “code for the coverage of the Colombian armed conflict”, this paper argues that journalism ethics needs to be understood not only as a matter of journalists. Ethics also depends on the context which journalists do their job. For example, in wartime, the reporting of news is influenced not only by the economic, symbolic and media constraints, but also by the strategic aims of the armed groups. Thus, ethics codes are more than documents in which journalists state how to do their job in a right way. Like the case of the Colombian armed conflict illustrates, ethics codes are documents in which journalists defend their independence, protect themselves from threats and argue for better work conditions. In this sense, ethics codes in wartime function more as political acts of communications rather than just training documents.